Respuesta :

Answer:

[tex]\frac{\bf{cd^7}}{\bf{c^6d \cdot c^4d^9}}=\frac{\bf{1}}{\bf{c^9d^3}}[/tex]

Step-by-step explanation:

Given expression is [tex]\frac{cd^7}{c^6d \cdot c^4d^9}[/tex]

[tex]\frac{cd^7}{c^6 d \cdot c^4d^9}=\frac{c d^7}{c^{10}d^{10}}[/tex] by using the formula [tex]a^m+a^n=a^{(m+n)}[/tex]

[tex]\frac{c d^7}{c^6 d\cdot c^4d^9}=\frac{c}{c^{10}}\cdot\frac{d^7}{d^{10}}[/tex]

[tex]\frac{c d^7}{c^6 d\cdot c^4d^9}=\frac{c^-9}{d^-3}[/tex] by using the formula  [tex]\frac{a^m}{a^n}=a^{(m-n)}[/tex]

[tex]\frac{c d^7}{c^6 d\cdot c^4d^9}=\frac{1}{c^9d^3}[/tex] by using the formula  [tex]\frac{1}{a^m}=a^{-m}[/tex]